Optimalisasi Pajak Progresif sebagai Instrumen Penertiban Tanah Terlantar: Studi Komparatif dan Rekonseptualisasi Kebijakan Pertanahan di Indonesia - Renald, Andi; Boer, Muhammad Riyan Kachfi (Widya Bhumi, 2025)
Following the enactment of Law Number 5 of 1960 concerning Basic Agrarian Principles (UUPA), the unification of land law in Indonesia restored the authority over land to the state and the Indonesian people. However, land tenure inequality persists due to the widespread abandonment of land, while public demand for land as a means of livelihood continues to rise. This study aims to analyze the optimization of land use through a juridical approach based on Government Regulation Number 20 of 2021 concerning the Control of Abandoned Areas and Land, using a comparative study of similar policies in several other countries. The findings reveal that Indonesia’s mechanism for regulating abandoned land has yet to make optimal use of fiscal instruments. In fact, tools such as progressive taxation, incentives, and tax relief based on land value taxation have proven effective in reducing land abandonment in various countries. These fiscal mechanisms serve a dual function: as a regulatory instrument that deters land neglect through economic disincentives and as a budgetary instrument that generates funds for regional development. This study recommends integrating such fiscal mechanisms into the provisions of Government Regulation Number 20 of 2021 as a preventive measure before the implementation of sanctions such as the revocation of rights and state repossession. Pascalahirnya Undang-Undang Nomor 5 Tahun 1960 tentang Peraturan Dasar Pokok-Pokok Agraria (UUPA), unifikasi hukum pertanahan telah mengembalikan penguasaan tanah kepada negara dan bangsa Indonesia. Namun, ketimpangan penguasaan tanah masih terjadi akibat banyaknya tanah yang ditelantarkan, sementara kebutuhan masyarakat akan tanah sebagai sumber penghidupan terus meningkat. Penelitian ini bertujuan menganalisis optimalisasi pemanfaatan lahan melalui pendekatan yuridis berdasarkan Peraturan Pemerintah Nomor 20 Tahun 2021 tentang Penertiban Kawasan dan Tanah Telantar, dengan studi komparatif terhadap kebijakan serupa di beberapa negara. Hasil penelitian menunjukkan bahwa mekanisme penertiban tanah telantar di Indonesia belum memanfaatkan instrumen fiskal secara optimal, padahal instrumen seperti pengenaan pajak progresif, pemberian insentif, dan relaksasi pajak berbasis Land Value Taxation telah terbukti efektif menekan penelantaran tanah di berbagai negara. Mekanisme pajak ini berfungsi ganda: sebagai instrumen regulerend yang memberikan efek jera bagi pemilik tanah, sekaligus sebagai instrumen budgeter yang menghimpun dana untuk pengembangan wilayah. Penelitian ini merekomendasikan integrasi mekanisme fiskal tersebut dengan ketentuan dalam PP Nomor 20 Tahun 2021 sebagai langkah preventif sebelum penerapan sanksi penghapusan hak dan penguasaan oleh negara.